Sintesis Nanopartikel Perak dan Pengaruh Penambahan Asam p-Kumarat Untuk Aplikasi Deteksi Melamin - R, Irwan; Zakir, Muhammad; Budi, Prastawa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Biosynthesis of silver nanoparticles (AgNPs) using mangosteen bark extract, modification and its application in detecting melamine has conducted. This research aimed to synthesize AgNPs via bio-reduction method using mangosteen bark extract followed by modification with p-coumaric acid (APK), and evaluating its application detecting melamine. The AgNPs were characterized through ultraviolet-visible absorption spectroscopy (UV-Vis), Fourier transform infrared absorption spectroscopy (FTIR), and X-ray diffraction (XRD). Observation suggested that an increase of incubation time had affected its surface Plasmon resonance trend. Observation of functional group by FTIR showed that carbonyl group (1707 cm-1) suspected from hydroxyl group (3414 cm-1). Further analysis of crystallite via XRD suggested that nanoparticle size at 30 nm estimated using Debye-Scherer, within the form of unit cells is cubic. Modified AgNPs showed an interaction between APK and particle surface through C=C alkenes (1598 cm-1) and aromatics (1672 cm-1), =C-H aromatic (3070 cm-1), aliphatic C-H (2501 cm-1), C-O (1107 cm-1) and C=O carboxylate (1774 cm-1). The performance of product as melamine detector suggested that the AgNPs-APK had detected melamine in range of concentration from 0.1 to 1000 ppm.